Nicolau Syndrome due to Penicillin Injection: A Report of 3 Cases without Long-Term Complication - Sara Memarian; Behdad Gharib; Mohammd Gharagozlou; Hosein Alimadadi; Zahra Ahmadinejad; Vahid Ziaee (Case Reports in Infectious Diseases)
Nicolau syndrome (NS) or livedo-like dermatitis is a rare complication of injection of various medications such as penicillin. The pathophysiology of this events is not clear, but some hypotheses are suggested, such as sympathetic nerve stimulation, embolic occlusion, inflammation, or mechanical injury. In this paper we report 3 cases of NS following benzathine penicillin. Clinical symptoms improved in 2 cases during 2-month follow-up, but one of them had a residual necrosis in the distal phalanges of the toes.